(untitled) (Research, Society and Development, 2024)
Introduction: Breast cancer is tha most common cause of death in the female population, this disease triggers many symptoms resulting from stressful moments. Its treatment has social and emotional consequences, among them, sleep is directly affected due to the entire disease process. Objective: To evaluate the quality of sleep of women with mastectomies after breast cancer. Methodology: The type of study is observational, descriptive, analytical, cross-sectional and quantitative in nature. The inclusion criteria include women undergoing mastectomies after breast cancer aged 18 to 59 years. As exclusion, women with lymphedema, breast reconstruction and cognitive disorders. The clinical and sociodemographic questionnaire and the Pittsburgh Index (PSQI) were applied. Results: Sample of 130 participants. Poor sleep quality prevailed in women aged 41 to 50 years, white race/color, professionally active, who sometimes practice physical activity, and underwent unilateral mastectomy. Regarding the PSQI, 9.2% reported “good” sleep, 46.9% “bad” sleep and 43.8% “sleep disorder”. And the occurrence of sleep disorders is more common in professionally inactive women. Conclusion: The scarcity of studies in the literature was a restrictive factor in the present research. However, knowing that poor sleep quality negatively impacts the lives of these women, more studies in the area are necessary to contribute to scientifically based interventions.